Transition to International Financial Reporting Standards: The Demand of the ERA and the Foundations for Implementation (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the concept of the development of International Financial Reporting Standards (IFRS), the process of transition in Uzbekistan, and the impact of IFRS on foreign investment. The main stages of the transition to IFRS, the problems encountered, and their potential solutions are considered.